Profiling of Long Non-coding RNAs and mRNAs by RNA-Sequencing in the Hippocampi of Adult Mice Following Propofol Sedation - Fan, Jun; Zhou, Quan; Li, Yan; Song, Xiuling; Hu, Jijie; Qin, Zaisheng; Tang, Jing; Tao, Tao (Frontiers in Molecular Neuroscience, 2018)
Propofol is a frequently used intravenous anesthetic agent. The impairment caused by propofol on the neural system, especially the hippocampus, has been widely reported. However, the molecular mechanism underlying the effects of propofol on learning and memory functions in the hippocampus is still unclear. In the present study we performed lncRNA and mRNA analysis in the hippocampi of adult mice, after propofol sedation, through RNA-Sequencing (RNA-Seq). A total of 146 differentially expressed lncRNAs and 1103 mRNAs were identified. Bioinformatics analysis, including gene ontology (GO) analysis, pathway analysis and network analysis, were done for the identified dysregulated genes. Pathway analysis indicated that the FoxO signaling pathway played an important role in the effects of propofol on the hippocampus. Finally, four lncRNAs and three proteins were selected from the FoxO-related network for further validation. The up-regulation of lncE230001N04Rik and the down-regulation of lncRP23-430H21.1 and lncB230206L02Rik showed the same fold change tendencies but changes in Gm26532 were not statistically significant in the RNA-Seq results, following propofol sedation. The FoxO pathway-related proteins, PI3K and AKT, are up-regulated in propofol-exposed group. FoxO3a is down-regulated at both mRNA and protein levels. Our study reveals that propofol sedation can influence the expression of lncRNAs and mRNAs in the hippocampus, and bioinformatics analysis have identified key biological processes and pathways associated with propofol sedation. Cumulatively, our results provide a framework for further study on the role of lncRNAs in propofol-induced or -related neurotoxicity, particularly with regards to hippocampus-related dysfunction.